The use of Australian SMART Recovery groups by people who use methamphetamine: Analysis of routinely-collected nationwide data. (1st August 2021) - Beck, Alison K.; Larance, Briony; Deane, Frank P.; Baker, Amanda L.; Manning, Victoria; Hides, Leanne; Shakeshaft, Anthony; Argent, Angela; Kelly, Peter J.
Highlights: This study adds new knowledge on methamphetamine-related service utilization. Methamphetamine was the second most common reason for attending SMART Recovery groups. People were more likely to attend for methamphetamine if male, aged <45, or regional. SMART Recovery groups had strong levels of facilitator rated group cohesion. Ratings remained strong irrespective of the group proportion attending for methamphetamine. Abstract: Introduction: Mutual support groups (e.g. SMART Recovery) are an important source of support for people experiencing addictive behaviours. Little is known about the use of mutual support groups by people who use methamphetamine, or the factors that may influence group cohesion. Methods: This study uses post-group data reported by SMART Recovery facilitators in Australia between 2018 and 2020. Group cohesion was indexed by facilitator ratings of The Group Entitativity measure (GEM-GP). Participant characteristics (gender, age, new or returning group member, voluntary or mandated attendance) and group location (major city vs. regional/remote vs. online) were used to (a) compare methamphetamine and non-methamphetamine related attendances; and (b) explore relationships to group cohesion within groups where the majority attended for methamphetamine. Results: Methamphetamine use was the second most common reason for attending SMART Recovery groups (n = 4929; 22.2 % service occasions). Methamphetamine-related service occasions were more likely amongst men, people aged <45 years, returning attendees and regional/rural groups (all p < .05). GEM-GP scores were high (signalling strong cohesion), and did not significantly differ according to proportion of participants attending for methamphetamine ( F (1, 2) = 0.482, p = .618). Group cohesion increased with larger group size, proportion of women and proportion of younger people ( F (4, 504) = 11.058, p < .001)). Discussion and conclusions: This study improves current understanding of service utilisation by people who use methamphetamine. SMART Recovery groups offer an avenue for supporting a diverse range of people who use methamphetamine, outside the formal treatment system. This provides an important foundation for improving community support options for people who use methamphetamine.